The influence of foreign equity and board membership on corporate strategy and management of internal costs in Portuguese banks - Gulamhussen, M. A.; Guerreiro, L. (Management Accounting Research, 2009)
This study examines the influence of foreign equity and board membership on corporate strategy and the management of internal costs of banks headquartered in Portugal using proprietary data maintained by the Central Bank. The findings reveal that foreign equity reduces both total and operating costs, and foreign board membership reduces domestic banks’ dependence on revenues from traditional areas of business and enhances the potential for generating revenues from non-traditional areas of business. These results are controlled for a variety of standard accounting ratios used in the literature. We argue that foreign equity and board membership forces banks to redirect corporate strategy and to reduce internal costs.